2012
DOI: 10.1371/journal.pone.0029855
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-1 and -9 in Human Placenta during Spontaneous Vaginal Delivery and Caesarean Sectioning in Preterm Pregnancy

Abstract: Preterm birth is a major public health problem in terms of loss of life, long-term and short term disabilities worldwide. The process of parturition (both term and preterm) involves intensive remodelling of the extracellular matrix (ECM) in the placenta and fetal membranes by matrix metalloproteinases (MMPs). Our previous studies show reduced docosahexaenoic acid (DHA) in women delivering preterm. Further omega 3 fatty acids are reported to regulate MMP levels. This study was undertaken to examine the placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
4
29
0
1
Order By: Relevance
“…This is consistent with our earlier study where we have reported a negative association between placental MMP9 levels and DHA levels in the whole cohort (Sundrani et al 2012). It is suggested that reduced omega 3 fatty acids may up regulate two-series prostaglandin release thereby increasing the levels of MMPs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is consistent with our earlier study where we have reported a negative association between placental MMP9 levels and DHA levels in the whole cohort (Sundrani et al 2012). It is suggested that reduced omega 3 fatty acids may up regulate two-series prostaglandin release thereby increasing the levels of MMPs.…”
Section: Discussionsupporting
confidence: 93%
“…Considering both mode of deliveries, there were 68 women in term labor and 66 women in preterm labor. The inclusion and exclusion criteria were the same as reported in our earlier study (Sundrani et al 2012).…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations